AKTUALISASI JATI DIRI BANGSA DALAM KESATUAN MENGHADAPI PANDEMI - Ria Karina; Natalis Christian; Iskandar Itan; Marco Nicholas Alfredo Loho; Winton Tan; Jessica Jessica; Jesslin Jesslin; Valen Oktavianti; Stella Stella; Marcelina Victoria; Venny Chou; Nydia Salsabila Firdaus (National Conference for Community Service Project (NaCosPro), 2020)
The COVID-19 pandemic has caused many negative effects on the economy of Indonesia. A number of citizens (regular workers) have lost their job, meaning they have lost their main source of income, which was the reason why the writer has chosen to do a distribution of food supplies to families in need, especially in Sub-district Nongsa Batam Island. In the process of making, there weren’t any unsolvable issues. The only issue that was considered a problem was asking for permission from the person-in-charge of the selected residence. The method of this activity is by fundraising, by posting in stories or feeds on Instagram.